(untitled) (World Bulletin of Management and Law, 2024)
Based on the study of the theoretical and practical aspects of lending to individuals in foreign banking practice, their advanced and modern aspects were determined. As a result of the study, the use of a number of nontraditional forms of lending to individuals in foreign banking practice, as well as the requirements for lending and the specific features of the process of its implementation, were determined. Taking this into account, some proposals and recommendations were developed regarding the application of their positive and advanced aspects in the banking practice of Uzbekistan